Social Contact Patterns in Rural and Urban Settings, Mozambique, 2021–2022 - Moses C. Kiti; Charfudin Sacoor; Obianuju G. Aguolu; Alana Zelaya; Holin Chen; Sara S. Kim; Nilzio Cavele; Edgar Jamisse; Corssino Tchavana; Americo Jose; Ivalda Macicame; Orvalho Joaquim; et al. (Emerging Infectious Diseases)
Few sources have reported empirical social contact data from resource-poor settings. To address this shortfall, we recruited 1,363 participants from rural and urban areas of Mozambique during the COVID-19 pandemic, determining age, sex, and relation to the contact for each person. Participants reported a mean of 8.3 (95% CI 8.0–8.6) contacts per person. The mean contact rates were higher in the rural site compared with the urban site (9.8 vs 6.8; p<0.01). Using mathematical models, we noted higher vaccine effects in the rural site when comparing empirical (32%) with synthetic (29%) contact matrices and lower corresponding vaccine effects in the urban site (32% vs 35%). Those effects were prominent in younger (0–9 years) and older (≥60 years) persons. Our work highlights the importance of empirical data, showing differences in contact rates and patterns between rural and urban sites in Mozambique and their nonnegligible effects in modeling potential effects of vaccine interventions.